A decision tree method for explaining household gas consumption: The role of building characteristics, socio-demographic variables, psychological factors and household behaviour. (March 2020) - Namazkhan, Maliheh; Albers, Casper; Steg, Linda
Abstract: This research aims to develop a decision tree model for understanding actual gas consumption in residential buildings. Extending previous studies, this study examined to what extent four different type of factors, building characteristics, socio-demographics, psychological factors and household behaviour can explain actual gas consumption of Dutch households in 2017 and 2018. Data were collected from 601 households. A novel approach, a decision tree method, revealed that household gas consumption was related to building characteristics, socio-demographics, and psychological factors, while energy-related behaviour in households was not uniquely related to gas consumption. Specifically, house size, building age and residence type (building characteristics), household income and employment status (socio-demographics), and most notably egoistic values, hedonic values, environmental self-identity, perceived corporate environmental responsibility of the energy provider, and social norm (psychological factors) predicted total actual household gas consumption. These results illustrate that the novel integrated framework introduced in the paper yields a better understanding of actual household gas consumption. The results have important practical implications and suggest that it would be important to target these three type of factors in policy aimed to reduce household gas consumption. Highlights: A novel analysis, a decision tree model, is presented to understand household gas use. Household gas-use depends on individual and building characteristics and their interaction. Psychological factors play an important role in explaining household gas use. Integrated frameworks yield a better understanding of household gas use.